Awareness and Utilization of PhilHealth’s Primary Care Benefit and KonSulTa (YaKap) Program Among Barangay Health Workers in Rural Kalinga, Philippines - Apilado, Hideko Apaling (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study looked at how aware Barangay Health Workers (BHWs) and their dependents are of PhilHealth’s Primary Care Benefit (PCB) and KonSulTa (YaKap) Program, and how often they use these services and change their health seeking behavior for health services such as proactive enrollment, routine consultations, and early intervention. This study was conducted in the selected rural municipalities of Kalinga, Philippines. Although the program was created to strengthen primary health care under the Universal Health Care Act, the findings suggest that many frontline health workers are not fully informed about the program or are not able to access its services easily. The study aimed to find out how familiar BHWs are with the different parts of the program and how often they use services such as enrollment, First Patient Encounter, medical consultations, diagnostic tests, and medicines. It also identified the common problems that prevent them from using these services. A total of 115 Barangay Health Workers (BHWs) were included in the study, which included structured questions and semi-structured interviews. Data were further subjected using cross-sectional descriptive research. Results revealed that awareness of the PCB/YaKap Program with 34.88% low awareness among respondents, limited utilization of 22.95%, and 76.18% have identified challenges, which includes inadequate information dissemination, procedural complexity, logistical challenges, inconsistent service availability, long waiting times and staffing limitations. The study also found that awareness and usage did not significantly differ based on age, sex, civil status, years of service, or educational background.